Effect of resuscitation training and implementation of continuous electronic heart rate monitoring on identification of stillbirth. (February 2022) - Patterson, Jackie; Berkelhamer, Sara; Ishoso, Daniel; Iyer, Pooja; Lowman, Casey; Bauserman, Melissa; Eilevstjønn, Joar; Haug, Ingunn; Lokangaka, Adrien; Kamath-Rayne, Beena; Mafuta, Eric; Myklebust, Helge; et al.
Abstract: Aim: To evaluate the effect of resuscitation training and continuous electronic heart rate (HR) monitoring of non-breathing newborns on identification of stillbirth. Methods: We conducted a pre-post interventional trial in three health facilities in the Democratic Republic of the Congo. We collected data on a retrospective control group of newborns that reflected usual resuscitation practice (Epoch 1). In the prospective, interventional group, skilled birth attendants received resuscitation training in Helping Babies Breathe and implemented continuous electronic HR monitoring of non-breathing newborns (Epoch 2). Our primary outcome was the incidence of stillbirth with secondary outcomes of fresh or macerated stillbirth, neonatal death before discharge and perinatal death. Among a subset, we conducted expert review of electronic HR data to estimate misclassification of stillbirth in Epoch 2. We used a generalized estimating equation, adjusted for variation within-facility, to compare risks between EPOCHs. Results: There was no change in total stillbirths following resuscitation training and continuous electronic HR monitoring of non-breathing newborns (aRR 1.15 [0.95, 1.39]). We observed an increased rate of macerated stillbirth (aRR 1.58 [1.24, 2.02]), death before discharge (aRR 3.31 [2.41, 4.54]), and perinatal death (aRR 1.61 [1.38, 1.89]) during the intervention period. In expert review, 20% of newborns with electronic HR data that were classified by SBAs as stillborn were liveborn. Conclusion: Resuscitation training and use of continuous electronic HR monitoring did not reduce stillbirths nor eliminate misclassification.